Entangled Territorialities : Negotiating Indigenous Lands in Australia and Canada - Dussart, Françoise; Poirier, Sylvie, 1953- (Book collections on Project MUSE., 2017)
Entangled Territorialities offers vivid ethnographic examples of how Indigenous lands in Australia and Canada are tangled with governments, industries, and mainstream society.